Evaluation on performance of square finned conformal cooling channel (sfccc) fabricated by selective laser melting (slm) on plastic moulded part - Kamarudin, Khairu (2019)
In plastic injection moulding (PIM) process, the cooling stage is the most important phase because it significantly affects the productivity and quality of the molded part. Thus, the cooling system need to be emphasized in designing the injection mould system. The application of conformal cooling channels which only can be fabricated by additive manufacturing technology (AM) are proven to increase the injection moulding performance and able to reduce the quality issues. This research introduced the Square Finned Conformal Cooling Channel (SFCCC) in the PIM as a way to enhance the performance of square shape conformal cooling channel (SSCCC) in PIM. The mould insert with SFCCC has been designed, simulated via finite element analysis software, fabricated (by combination of High Speed Machining and Selective Laser Melting (SLM)), and tested using a front panel housing as the injected part for the case study. Eight types of variate SFCCC design (SFCCC 1 to SFCCC 8) employing finned and sub groove concept were analysed via simulation work to determine the best design in terms of shortest cooling time. The results showed that the shortest cooling time recorded by SFCCC 8 was at 7.621 sec, an improvement of 16.44% compared with SSCCC. In terms of cycle time, the SFCCC is able to improve the SSCCC by 8.33% to 10.26%. Meanwhile, in comparison with industrial mould using Milled Groove Conformal Cooling Channel (MGCCC), the SFCCC showed an improvement of 19.60% to 39.36% based on the coolant temperature. The experimental results showed the greatest shrinkage in the X-direction at 0.93% and the smallest shrinkage at 0.6%. For the Y-direction, the greatest shrinkage is 0.97% and the smallest shrinkage is 0.39%. In comparison with the injected part via MGCCC, the SFCCC had a slightly greater overall shrinkage in relation to the shrinkage and warpage at points X and Y direction. Most front panel housing shrinkage and warpage values in the experimental study were smaller than those of the simulative study. However, the experimental results were in line with the simulative results, proving that the SFCCC design had better cycle times and acceptable quality for an industrial mould.